Development of Enactive, Iconic, and Symbolic-Based Word Wall Media to Improve Elementary School Students' Writing Skills - Intan Khairani; Sakholid Nasution (MASI Mandiri Edukasi, 2025)
This research addresses the low writing ability among third-grade students at SD Negeri No. 106214 Sei Parit. The study aims to develop and examine the effectiveness of a “Word Wall” learning media based on the enactive, iconic, and symbolic approach to improve students’ writing skills. The research employed the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The validation results showed that the developed media was feasible to use, obtaining scores of 84.6% from media experts and 80% from material experts. The effectiveness test also indicated a significant improvement in students’ writing achievement, with the average score increasing from 40.95 to 85.6 and an N-Gain of 0.8 (high category). In addition, the practicality assessment showed that the media was practical to implement, with teacher responses reaching 84.2% and student responses reaching 75.7%. Thus, the Word Wall media is categorized as feasible, effective, and practical for enhancing elementary students’ writing skills.